Evaluating acceleration impact asymmetries during sprinting: Analyzing leg and track lane disparities among national athletes - Paz-Paz, E. O.; Pérez-Soriano, P.; Encarnación-Martínez, A. (European Journal of Sport Science, 2025)
Sprinting on bends demands biomechanical adjustments compared with straight-line sprinting that results in asymmetrical force production in the lower extremities. This study aimed to assess acceleration impacts in the lower extremity and impact transmission when sprinting on bend versus straight lanes. Eight experienced sprinters (age 16.3 ± 1.7 years, mass 58.5 ± 11.4 kg, and height 1.72 ± 0.10 m), specializing in the 100, 200, and 400 m events, ran two bouts of 60 m lane heats at maximum speed on the straight lane and bend lanes one and eight (with radii of 37 and 45.10 m, respectively) of a standard 400 m track. Accelerometers on the tibias and head recorded acceleration impacts. Results revealed higher impact magnitudes in the outside leg during bend sprints compared with the inside leg (p < 0.05). Additionally, bend lanes exhibited higher impact magnitudes compared with the straight lane (p < 0.05). Asymmetrical acceleration impacts were observed during bend sprints, with greater asymmetry compared to straight sprints. However, the distribution of impact forces between the legs did not appear to be influenced by lane radius. This suggests that the specific biomechanical demands of bend sprinting differ significantly from those of straight sprinting. These findings emphasize the need for coaches to account for increased asymmetry and distinct impact patterns when training athletes for bend sprints compared to straight-line sprints.